Is rosacea a risk factor for cancer: A population-based cohort study in Taiwan - Tsung-Hsien Chang; Hsiu J Ho; Yun-Ting Chang; Chung-Pin Li; Chun-Ying Wu; Chen-Yi Wu (Wolters Kluwer Medknow Publications, 2020)
Background: Rosacea is a chronic inflammatory skin disease with mounting evidence associating it with systemic disorders. Cancer, induced or facilitated by chronic inflammatory microenvironment, shares common pathogenic mechanisms with rosacea. Objectives: We performed a population-based cohort study to investigate the risk of developing cancer among people with rosacea in Taiwan. Methods: A total of 65,526 patients with rosacea and 262,104 age-, sex-, and comorbidity-matched controls were identified from the Taiwan's National Health Insurance Research Database between 1997 and 2013. All participants were followed up for 2-12 years. Incidence rates (IRs) of overall and specific types of cancer were calculated. Cumulative incidences of cancer were compared between the two cohorts by Kaplan-Meier method and modified log-rank test. Hazard ratios (HRs) adjusted for age, sex, and comorbidities for overall and specific malignancies were estimated using subdistribution proportional hazard models. Results: The IR (per 1000 person-years) of cancer was 2.83 in patients with rosacea and 3.00 in controls. There was no difference in cumulative incidence of cancer between patients with or without rosacea (P = 0.109). The risk of developing cancer did not increase among patients with rosacea (HR = 1.04; 95% confidence interval = 0.98-1.11). In addition, patients with rosacea did not have a significantly increased risk of developing any specific type of cancer. Conclusion: We found no association between rosacea and malignancy. These results did not agree with those reported in previous studies. Further research should be conducted to clarify the association between rosacea and cancer, especially focusing on the pathophysiology.